Strategi Pembelajaran SD/MI - Ade Rahayu; Dewi Anjarsari; Kumaidi Kumaidi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Effective learning at the elementary school level requires the selection of instructional strategies that are aligned with students’ developmental characteristics, learning objectives, and educational contexts. This article aims to comprehensively review various instructional strategies relevant to elementary education, including Problem Based Learning, Project Based Learning, Contextual Teaching and Learning, cooperative learning models (Jigsaw, Student Teams Achievement Divisions, Teams Games Tournament, Two Stay Two Stray, and Numbered Heads Together), Inquiry Learning, Discovery Learning, Role Playing, the SAVI approach, and Reward and Punishment. This study employed a literature